Teaching of sciences and mathematics: an analysis of theses of the south of Brazil (Research, Society and Development, 2019)
The aim of understand the impact on elementary education of scientific productions, doctoral level, in the area of science and mathematics education, in the Southern Region of Brazil. It is discussed research results developed under PROBIC/FAPERGS, Franciscan University. It was a quantitative/qualitative study, involving mapping of theses produced between 2013-2017. For this article, we focused on the Southern region, where 6 PPGs and a total of 159 published theses were found. In the qualitative analysis, the results were categorized as: the objectives, the methodology and the impacts in the basic education. Postgraduate studies have had less impact than the intended quality of basic education.